Para além de uma dúvida razoável: Serial e a busca da verdade - Diogo Tognolo Rocha (2018)
This work aims to investigate how truth is understood by the narrator and listeners of the Serial podcast. The show features a reinvestigation of a murder case, casting doubts about the real culprit of the crime. Its listeners have also undertaken a search for the truth, making Serial a fruitful program to analyze the knowledge relations that emerge. We understand this phenomenon from a broad perspective that puts it in dialogue with other genres and formats, such as journalism, detective stories and fictional television series. Thus, our reading of Serial does not only comprehend the podcasts episodes, but views it as one of the nodes of a textual network constantly refigured by the program itself and its listeners. To understand how the narrator and listeners establish a game for the willingness to know, we analyze these figures from their origins in literature, making the appropriate adaptations for the analysis of an audio product, and putting in discussion the changes made by the fact that Serial is a product that circulates on the internet, in a serialized way. With this, we seek to discuss the search for truth carried out by the podcast and the introduction of doubt as a central element, understanding the strategies that the narrator uses to put herself as a figure endowed with reliability, and the actions carried out by the listeners, who seek to fill and extend the gaps offered by Serial.